Characterization and properties of durian skin fiber filled polylactic acid/polypropylene compatibilized with glut palmitate salt / Nor Mazlina Abdul Wahab … [et al.] - Abdul Wahab, Nor Mazlina; Mohamad, Sarina; Fizal, Nurul Syafawani; Samsudin, Dalina; Mustafa, Mohd Syamaizar (Research Management Institute (RMI), 2023)
PLA matrix provides good mechanical, physical and degradability properties, but somehow PLA alone is not good enough to produce a product as PLA has poor toughness resulting a brittle material. Natural fiber such as Durian skin fiber (DSF) can be incorporated into PLA/PP as a biopolymer to achieve the desired properties and better degradation which resulting a good bio-composite. Therefore, the study was carried out to produce bio-composite of DSF filled with PLA/PP and glut palmitate (GP) salt as compatibilizer. The bio-composites was successfully developed using different filler (DSF) loadings (0 php, 15 php, 30 php, 45 php and 60 php) with melt mixing blending. The FTIR analysis showed the new peak existed at 1595 cm-1 revealed a good interaction in the composite system which come from the bending of NH2 vibration from GP. The mechanical properties (tensile properties) and physical properties (water absorption ability and density) of prepared bio-composite were determined. Increasing of DSF filler loading to 60 php DSF in PLA/PP bio-composite with the addition of GP increased in tensile strength (5.06 ± 0.09 MPa) and elongation at break (3.74 ± 0.18 %) due to enhanced interfacial bonding and strong adhesion between the polymer matrix and the filler due to the presence of compatibilizer. However, increased filler loading to 60 php DSF, showed a decreasing trend in the tensile modulus which represents high flexibility of the bio-composites.